Meretas Tantangan Baru: Studi Komparasi Desentralisasi Pengelolaan Pesisir di Indonesia Timur - Siry, Hendra Yusran (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2009)
The mandate of article 18 Law 32/2004 is about the authority given to regency government by local government in managing the shoreline and resources contained, but it has to be suitable with local characteristic which one third away from province government authority area. This kinds of decentralization demands on not only an equipped government, but also government responsiveness in managing the shoreline based on justice and sustainability values for those local stakeholders whom in charge. But the obstacles were appeared such as lack of personnel, minimum budget, and poor equipment and document (P3D) in implementing shoreline decentralization. This paper explores the role taken by local politics that surely appeared in shoreline management. Refers to the results of field study that had be done in 2005 and 2007 based on qualitative research method, this paper show the comparative study between two regencies in the eastern island in Indonesia, Pangkajene Island and Konawe. Comparison between these two regencies offers three important reviews on shoreline management. It did not only reveal a contrast outlook and experience at management mechanism in shoreline, but also highlighted the varied managements and obstacles which can be very much enriching of shoreline has been triggered and increased patterns of management and important roles for local stakeholders in dealing with new obstacles in shoreline management.